Development of a valvetrain mechanism (actuation of exhaust rotary valve) for a small two stroke engine design - 296661 Lee, Chang Quan (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2005